Affiliation: bodhisattva gotra (Short Notes on gotra Theory in Yogācāra Buddhism) - Korobov, Vladimir (Acta Orientalia Vilnensia, 2005)
Centre of Oriental Studies, Vilnius University The article continues discussion on ontological entities in Yog